2017
DOI: 10.24925/turjaf.v5i7.773-779.1182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dietary Supplementation of Some Antioxidants on Liver Antioxidant Status and Plasma Biochemistry Parameters of Heat-Stressed Quail

Abstract: This study aimed to compare the dietary supplementation of oleuropein (O) and α-tocopherol acetate (TA) alone or with organic selenium (Se) on liver antioxidant status and some plasma biochemistry parameters in Japanese quails reared under heat stress (HS). A total of 800, two-weeks old quails were kept in wire cages in the temperaturecontrolled rooms at either 22°C or 34°C for 8 h/d and fed on a basal diet (NC) or the diets supplemented with TA (TA200) or O (O200) at 200 mg/kg alone or with OSe (TA200+OSe and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 25 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…In contrast, other researchers reported that the serum TAS was not affected by dietary vitamin E supplementation in broilers [ 38 ] and laying hens [ 41 ]. In the same line, a recent study reported that the supplementation of vitamin E in Japanese quail diets reduced the serum total cholesterol and triglycerides [ 42 ]. This finding supports previous studies [ 37 , 39 , 40 ], who reported a reduction of the serum total cholesterol of birds fed a vitamin E-supplemented diet under heat stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, other researchers reported that the serum TAS was not affected by dietary vitamin E supplementation in broilers [ 38 ] and laying hens [ 41 ]. In the same line, a recent study reported that the supplementation of vitamin E in Japanese quail diets reduced the serum total cholesterol and triglycerides [ 42 ]. This finding supports previous studies [ 37 , 39 , 40 ], who reported a reduction of the serum total cholesterol of birds fed a vitamin E-supplemented diet under heat stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of olive pulp (50 and 100 g/kg), both GSH and GSR levels were improved but no significant effect was reported for UA and TBARS levels in the blood after 6 weeks of supplemented diet [81]. Likewise, the addition of oleuropein (200 mg/kg) was also associated with increased antioxidant capacity and reduced oxidative stress in the liver of Japanese quail [82].…”
Section: Antioxidant Activity In Vivo In Meat-producing Animalsmentioning
confidence: 90%
“…Turkez et al ( 2012) [169] reported that olive leaf extract showed beneficial influences against the genetic and oxidative damage of permethrin by increasing TAS and reducing TOS in rats. Oleuropein supplementation increased TAS and reduced TOS in quails subjected to heat stress [170].…”
Section: Oxidative Statusmentioning
confidence: 90%